The efficacy of homeopathic Arnica montana 200 CH on dental surgical treatments: a double-blind, placebo-controlled study - Erkan, Erhan; Parpar, Kudret; Develi, Tuba; Gündoğar, Mustafa; Gürler, Gökhan (The European Research Journal, 2019)
Objectives: The aim of this placebo-controlled study was to assess the efficacy of single dose homeopathic Arnica montana 200 CH in dental surgeries. Methods: The study included 79 patients undergoing wisdom teeth extractions, implant placements, cystectomies, augmentation procedures, alveoloplasties, lefort-1 osteotomies at Istanbul Medipol University’s Department of Oral and Maxillofacial Surgery. The patients were randomly divided into two groups using a computer program. Three globulesof Arnica montana 200 CH were administered in the sublingual area in the patients group 1, and glucose globules were administered in the sublingual area in the patients into group 2. After each patient’s surgical operation, the surgeoncompleted a survey about operation time and scope. In addition,a self-assessment survey was completed by the patients the day after their operationsto evaluate their post-operational swelling and pain. Results: Arnica montana did not appear to significantly prevent post-operative swelling and pain when compared to the placebo (p < 0.05). Conclusions: This study showed that the use of Arnica montana before a physically traumatic procedure is not more effective than the use of a placebo. However, the results should be evaluated in other studies, including the administration of Arnica montana after a physically traumatic procedure to clearly demonstrate its homeopathic efficiency.